Total fertilization failure with in vitro fertilization-intracytoplasmic sperm injection related to WEE2 mutation highlights emerging importance of genetic causes of in vitro fertilization failure - Hillary S. Weiner, M.B.E; Nicole D. Ulrich, M.D; Lauren Hipp, M.S., C.G.C; Ahmad Hammoud, M.D; Min Xu, Ph.D; Samantha B. Schon, M.D (Elsevier, 2022)
Objective: To report a unique case of total fertilization failure (TFF) after in vitro fertilization with intracytoplasmic sperm injection related to homozygous WEE2 gene mutation and summarize the current literature and management of TFF. Design: Case report. Setting: Academic fertility center. Patient(s): A 25-year-old woman and her 35-year-old partner with a history of near-complete fertilization failure after 2 cycles of in vitro fertilization/intracytoplasmic sperm injection. Intervention(s): Consultation with medical and commercial genetic testing for WEE2, PLCZ1, and TLE6. Main Outcome Measure(s): Oocyte fertilization. Result(s): The patient was homozygous for WEE2 pathogenic variant impacting oocyte activation and resulting in infertility. Conclusion(s): In the setting of TFF, early consideration should be given to genetic testing to assist couples in clinical decision-making and help limit the financial and emotional burden associated with unsuccessful fertility intervention.